The Role of Carbon Trading in Climate Change Mitigation: A Juridical Analysis of Policies and Regulations in Environmental Law in Indonesia - Rahmawati, Diah Ayu; Haryono, Haryono; Endarto, Budi; Soraya, Joice; Nurani, Juli (Eastasouth Institute, 2024)
This paper examines the role of carbon trading in climate change mitigation through a juridical analysis of Indonesia's environmental law and regulatory frameworks. Carbon trading has emerged as a critical tool for reducing greenhouse gas emissions, but its success depends on the strength of the legal and regulatory systems supporting it. By analyzing Indonesia’s Carbon Economic Value policy, environmental laws, and international commitments such as the Paris Agreement, this study identifies key regulatory gaps, overlapping jurisdictional issues, and enforcement challenges. The findings highlight the need for stronger monitoring, reporting, and verification mechanisms, as well as clearer regulatory frameworks to ensure the effectiveness of carbon trading in Indonesia. Recommendations are made to enhance institutional capacity, align national policies with international standards, and promote private sector participation. These improvements are crucial for achieving Indonesia’s emissions reduction targets and contributing to global climate change efforts.